Evaluation of the Skin Cracker Production Process at Skin Cracker SMEs - Ahmad Syafruddin Indrapriyatna; Reinny Patrisina; Asi Siva Dea; Nahda Sulasi; Yonithri Sherlyn (JTI: Jurnal Teknik Industri, 2026)
XYZ SME is a small and medium enterprise (SME) based in Padang, West Sumatra, specializing in traditional skin crackers (locally known as kerupuk jangek a traditional cowhide-based cracker). The company faces critical challenges related to hygiene and production inefficiencies, particularly delays during drying and frying stages, as well as inefficient material flow due to a suboptimal facility layout. This study employs Lean Manufacturing tools to identify and reduce production waste. The methodology incorporates the Waste Assessment Model (WAM) to quantify waste types, Value Stream Mapping (VSM) to visualize the production process, and Value Stream Analysis Tools (VALSAT) to prioritize improvement strategies. WAM analysis identified transportation (21.277%), inventory (17.021%), and waiting time (14.894%) as the most significant waste categories. The initial Process Cycle Efficiency (PCE) was measured at 41.82%. Improvement proposals included enhanced GMP practices through training, supervision, and infrastructure upgrades, as well as production efficiency measures such as layout redesign, improved worker discipline, and the use of cost-effective machinery. These interventions led to a projected PCE of 95.24%, indicating substantial improvements in workflow efficiency.